2021
DOI: 10.1111/1541-4337.12749
|View full text |Cite
|
Sign up to set email alerts
|

Structural breakdown of starch‐based foods during gastric digestion and its link to glycemic response: In vivo and in vitro considerations

Abstract: The digestion of starch‐based foods in the small intestine as well as factors affecting their digestibility have been previously investigated and reviewed in detail. Starch digestibility has been studied both in vivo and in vitro, with increasing interest in the use of in vitro models. Although previous in vivo studies have indicated the effect of mastication and gastric digestion on the digestibility of solid starch‐based foods, the physical breakdown of starch‐based foods prior to small intestinal digestion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 263 publications
(387 reference statements)
0
32
1
Order By: Relevance
“…According to Liu et al ( 33 ), the differences between samples can be explained by the number of amylose lipid complex, the different degrees of close packing mode of the double-helix structure and double helix orientation within crystal lamellae, leading to various perfect crystallite numbers and sizes of each extrudate. In addition, EPS had a lower Rc but lower digestibility than that of the other starches, possibly because EPS has a larger number of superhelix structure formed by linear amylose and amylopectin compared to that of the other samples ( 27 ). A similar study reported that the Rc of extruded rice starch was 4.4–6.5% ( 33 ).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…According to Liu et al ( 33 ), the differences between samples can be explained by the number of amylose lipid complex, the different degrees of close packing mode of the double-helix structure and double helix orientation within crystal lamellae, leading to various perfect crystallite numbers and sizes of each extrudate. In addition, EPS had a lower Rc but lower digestibility than that of the other starches, possibly because EPS has a larger number of superhelix structure formed by linear amylose and amylopectin compared to that of the other samples ( 27 ). A similar study reported that the Rc of extruded rice starch was 4.4–6.5% ( 33 ).…”
Section: Resultsmentioning
confidence: 98%
“…EWS had the loosest and most void-distributed granule surfaces. EWS molecules may break more easily during the hydrolysis of amyl-glucosidase and α-amylase than the other samples, whereas EPS showed significant opposite trend ( 27 ). Similarly, Faraj et al ( 18 ) showed that the degree of damage to the extrudate granule morphology of different types of barley flour significantly differed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to the in vitro assay, the extrudates were ground into a fine powder form (Section 2.6), which partly explained the rapid starch hydrolysis rates of the milled samples in the initial 20 min of the enzymatic hydrolysis (Figure 3A and B). However, in the real‐life setting, dogs most likely consume such dry pet foods in a pellet form with limited chewing, the matrix structure of which may play a vital role in determining the starch digestion rate in vivo (Mishra et al., 2012; Nadia et al., 2021). After being chewed to a limited level, in vivo digestion rates of pet food pellets having good integrity may not be as fast as the in vitro enzymatic hydrolysis rates of finely milled samples analyzed in the present study.…”
Section: Resultsmentioning
confidence: 99%